2014
DOI: 10.1515/dmdi-2013-0067
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of drug metabolizing enzymes in Brazilian populations

Abstract: Phase I and II drug metabolizing enzymes (DMEs) play an important role in biotransformation of endogenous and exogenous compounds including drugs currently used in pharmacoterapy. Moreover, the genetic variability of DMEs causes important interindividual differences in drug and metabolite exposure, drug response, and risk of adverse drug reactions. We reviewed pharmacogenetics/pharmacogenomics (PGx) studies that evaluated the influence of polymorphisms in the CYPs genes - mainly CYP1, CYP2 and CYP3 gene famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 103 publications
(145 reference statements)
0
1
0
Order By: Relevance
“…As the most important detoxification organ, the liver contains most of the phase I and phase II metabolic enzymes, which affect the metabolism of endogenous and exogenous substances (29) . KEGG pathway analysis revealed that metabolism of xenobiotics Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As the most important detoxification organ, the liver contains most of the phase I and phase II metabolic enzymes, which affect the metabolism of endogenous and exogenous substances (29) . KEGG pathway analysis revealed that metabolism of xenobiotics Fig.…”
Section: Discussionmentioning
confidence: 99%